Islamic Governance dalam Tata Kelola Bisnis Pesantren: Model Konseptual Keberlanjutan Ekonomi Lembaga - Abd Adim; M. F. Hidayatullah; Abdul Wadud Nafis (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Islamic boarding schools (pesantren) are no longer viewed solely as religious educational institutions but also as socio-economic entities that play a strategic role in community empowerment and the development of the Islamic economy. The emergence of various pesantren business units, including Islamic cooperatives, Islamic microfinance institutions, agribusinesses, and service enterprises, reflects the transformation of pesantren into productive and economically independent institutions. However, many pesantren continue to face challenges in achieving economic sustainability, including weak governance systems, limited managerial professionalism, inadequate human resources, and excessive dependence on charismatic leadership. This study aims to develop a conceptual model of pesantren business governance based on Islamic governance principles to achieve institutional economic sustainability. Using a qualitative approach and library research method, this study analyzes relevant literature on pesantren economics, Islamic governance, sustainability, and risk management. The findings indicate that sustainable pesantren economic development requires the integration of Islamic governance values, namely amanah (trustworthiness), transparency, justice, and maslahah (public benefit), with modern management systems and comprehensive risk management practices. The study proposes a conceptual governance framework linking pesantren resources, sharia governance, professional management, and risk mitigation as key determinants of economic independence and institutional sustainability. This framework is expected to provide strategic guidance for strengthening pesantren-based economic development in a sustainable and socially beneficial manner.